Representation of Character Education in The Movie Jumbo: A Semiotic Analysis - Ririn Nurul Azizah; Sitni Karimatan Nisa (LITERATUR : Jurnal Bahasa dan Sastra, 2025)
Character education is education that develops cultural values and national character so that individuals possess and apply these values in their lives as members of society and citizens who are religious, productive, and creative. Film is a popular medium that not only serves as entertainment but also as a means of character education.This study aims to analyze the representation of character education values in an Indonesian animated film titled Jumbo through Roland Barthes' semiotic approach. The analysis focuses on visual and verbal signs that represent character values such as nationalism, integrity, discipline, responsibility, cooperation, creativity, and social awareness. The research method used is descriptive qualitative with data collection techniques from watching and recording scenes, dialogues, and visual symbols in the film. The results of the analysis show that each scene contains denotati.ve, connotative, and mythical meanings that are interrelated, thus forming a contextual and implicit representation of character education values. The film Jumbo features the character Don, who faces bullying, the loss of his parents, and social challenges, but is guided by his family and friends to develop courage, empathy, and integrity. The interactions between characters, visual symbols, and the film's storyline are able to instill moral and social values in child and adolescent audiences. Thus, this film is not only a medium of entertainment but also serves as an effective educational tool for the internalization of character values, in line with the Character Education Strengthening Program (PPK) in Indonesia